PTH-025 Dietitian-led Virtual Coeliac Disease Clinic Results In Cost Savings And Increased Patient Satisfaction. (9th June 2014) - Stuckey, C; Martin, H; McLaughlin, S
Abstract : Introduction: We identified that demand for follow up of adult patients diagnosed with coeliac disease exceeded the capacity of our dietitian-led coeliac annual review clinic. A dietitian-led virtual coeliac clinic was developed as an efficient and cost effective method of reviewing adults with established coeliac disease. Methods: Patients with established coeliac disease (i.e. a combined histological and serological diagnosis more than 12 months earlier), who were assessed by the dietitian as understanding fully how to adhere to a gluten free diet and who have shown a good symptomatic response were sent the virtual clinic questionnaire. They were also sent a blood form to monitor full blood count, bone biochemistry, ESR, haematinics and tissue transglutaminase in line with the BSG 2010 coeliac guidelines. They were asked to complete and return the questionnaire in a prepaid addressed envelope and have the blood tests undertaken within 4 weeks. The questionnaire responses and blood results were reviewed by a specialist gastroenterology dietitian. The identification of any new abnormal blood results was highlighted to the GP and/or consultant gastroenterologist. If any red flag symptoms (i.e. blood in stools, unintentional weight loss or persistent change in bowel habit) were highlighted on the questionnaire then the patient was telephoned by the dietitian to discuss further before being referred to their GP or gastroenterologist as appropriate. Results: 86 patients were sent the virtual coeliac review questionnaire from May 2012- April 2013. Of these, 81 patients (94.2%) returned their questionnaire and 78 patients (90.6%) had their blood tests undertaken. Of these, 7.4% patients (n = 6) were referred to gastroenterology for abnormal blood results or for the presence of new gastrointestinal symptoms. Only 1 of these patients (1.2%) needed to be seen in the gastroenterology clinic. 6.1% of patients (n = 5) were telephoned by the dietitian for reporting red flag symptoms. After the telephone consultation none of these patients required gastroenterology or dietetic appointments. 80% of patients responded that alternating annually between virtual review and a clinic appointment was preferential to an annual clinic appointment. Conclusion: A virtual review coeliac clinic at the Royal Bournemouth Hospital is a cost effective and patient preferred method of managing adults with established coeliac disease. Reference: 1 The Management of Adults with Coeliac Disease; BSG 2010 Disclosure of Interest: None Declared.